A nanoscale ferroferric oxide coated biochar derived from mushroom waste to rapidly remove Cr(VI) and mechanism study. (September 2019) - Wang, Can; Tan, Hang; Liu, Huakang; Wu, Bin; Xu, Fei; Xu, Heng
Abstract: We developed a magnetic nano-material from spent Lentinula edodes substrate (LES), which was coated with nano-magnet after carbonization to remove Cr(VI). LES was given polyporous and crinkly surface structure after carbonization and the iron modification, which significantly improved its Cr affinity. X-ray diffraction analysis verified nano-Fe3 O4 crystal formation on LES biochar (LBC) surface and the possible existence of grimaldiite. X-ray photoelectron spectroscopy analysis manifested the reduction of Cr(VI) to Cr(III). The maximum removal rate of Cr(VI) by LBC-Fe3 O4 reached 99.44%. Taguchi experiment indicated the removal rate was mainly determined by Cr(VI) concentration, dosage, and pH. Furthermore, LBC-Fe3 O4 maintained 78.56% of its initial Cr(VI) removal efficiency after seven regenerations, indicating its fabulous stability. LBC-Fe3 O4 also presented efficient removal of multi-pollutants including Cu, Ni, Pb, COD, NH4 -N, etc. in practice. This research proved that LBC-Fe3 O4 could be applied for the treatment of Cr(VI) influenced liquid and recycling of agricultural waste. Graphical abstract: Unlabelled Image Highlights: Mushroom waste derived biochar coated nano-iron to remove Cr. Crystallization of Cr was found after adsorption and reduction. Great durability and stability under environmental variation and recycle.